Perencanaan Jalur Interpretasi Lanskap Kawasan Wisata Sejarah Candi Kerajaan Singosari Berbasis Aplikasi Android - Budiyono, Debora; Putri, Sri Andika; Aldy, Riyantina Fitra (Jurnal Lanskap Indonesia, 2025)
The temples of the Singosari kingdom function as places of worship for Hindu-Buddhist believers, educational facilities for the introduction of the history of the Singosari kingdom, architectural buildings, local community culture, landscape plants, and historical attractions. The existence of several temples of the Singosari kingdom that are scattered in several areas of Malang regency as potential historical tourism has not been followed by the planning of android application-based interpretation paths. The research objective was to plan a model of the Singosari kingdom temple tourism area landscape interpretation path based on an android application. The research method used in general was descriptive quantitative. The research location was carried out in the landscape of Kidal Temple, Jago Temple, Singosari Temple, and Sumberawan Temple. Research analysis through spatial analysis, Focus Group Discussion (FGD) analysis, analysis of tourist perceptions and preferences, and visual landscape analysis. The results showed that the landscape of Kidal Temple, Jago Temple, Singosari Temple, and Sumberawan Temple has the potential to be developed as a historical tourism area landscape. Planning is made based on the analysis of tourism potential, distance, and visit time that can be traveled by tourists in one visit to the specified object. The interpretive path planning model is the regional tour pattern. The regional tour pattern model is a travel pattern developed from the main destination because there are different tourist attractions located in close proximity. The interpretation path is divided into two tour packages, namely day visits and two-day visits.